Determinasi Tingkat Pengangguran di Provinsi Jawa Timur: Pendekatan Model Data Panel - Suryati Setiani (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2025)
This study aims to analyze the determinants of the Open Unemployment Rate (TPT) in East Java Province during the 2017-2024 period using a panel data regression approach. The independent variables analyzed include population, Gross Regional Domestic Product (GRDP), expected years of schooling, district/city minimum wage, and poverty rate. The data was obtained from the Central Statistics Agency and analyzed using three model approaches, namely the Common Effect Model (CEM), the Fixed Effect Model (FEM), and the Random Effect Model (REM), with the FEM selected as the best model based on the Chow and Hausman tests. The results showed that economic growth and the poverty rate have a significant effect on TPT, each with a negative and positive direction. Meanwhile, the minimum wage has a significant positive effect on unemployment, while the population and the human development index do not show a significant effect. These findings indicate the need to formulate employment policies that are more focused on improving the quality of economic growth and poverty alleviation to reduce the unemployment rate at the regional level.